Myelin oligodendrocyte glycoprotein revisited—sensitive detection of MOG-specific T-cells in multiple sclerosis. (August 2019) - Bronge, Mattias; Ruhrmann, Sabrina; Carvalho-Queiroz, Claudia; Nilsson, Ola B.; Kaiser, Andreas; Holmgren, Erik; Macrini, Caterina; Winklmeier, Stephan; Meinl, Edgar; Brundin, Lou; Khademi, Mohsen; Olsson, Tomas; et al.
Abstract: Autoreactive CD4 + T-cells are believed to be a main driver of multiple sclerosis (MS). Myelin oligodendrocyte glycoprotein (MOG) is considered an autoantigen, yet doubted in recent years. The reason is in part due to low frequency and titers of MOG autoantibodies and the challenge to detect MOG-specific T-cells. In this study we aimed to analyze T-cell reactivity and frequency utilizing a novel method for detection of antigen-specific T-cells with bead-bound MOG as stimulant. Peripheral blood mononuclear cells (PBMCs) from natalizumab treated persons with MS (n = 52) and healthy controls (HCs) (n = 24) were analyzed by IFNγ/IL-22/IL-17A FluoroSpot. A higher number of IFNγ (P = 0.001), IL-22 (P = 0.003), IL-17A (P < 0.0001) as well as double and triple cytokine producing MOG-specific T-cells were detected in persons with MS compared to HCs. Of the patients, 46.2–59.6% displayed MOG-reactivity. Depletion of CD4 + T-cells or monocytes or blocking HLA-DR completely eliminated the MOG specific response. Anti-MOG antibodies did not correlate with T-cell MOG-responses. In conclusion, we present a sensitive method to detect circulating autoreactive CD4 + T-cells producing IFNγ, IL-22 or IL-17A using MOG as a model antigen. Further, we demonstrate that MOG-specific T-cells are present in approximately half of persons with MS. Graphical abstract: Image 1 Highlights: MOG-specific pro-inflammatory CD4 + T-cells are present in half of MS-patients. MOG-specific T-cells exhibit Th1 and Th17 phenotypes and are HLA-DR restricted. MOG-specific T-cell responses do not correlate with anti-MOG antibody titers. Activation of T-cells in PBMCs using bead-bound antigen is highly antigen-specific.